EXPERIMENTAL AND FINITE ELEMENT ANALYSIS OF UNIDIRECTIONAL AND BIDIRECTIONAL FIBRE REINFORCED COMPOSITE CANTILEVER PLATES - PATIL CHETAN D.; PATIL R. D (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In vibration analysis mechanical resonance is a significant term. Resonance occurs when the frequency of its oscillations matches with the system’s natural frequency of vibration. It may cause extreme swaying motion and the Structural failure in offensively constructed structures like bridges, buildings and airplane. This type of failure is known as resonance disaster. To avoid structural damages caused due to resonance, it is important to determine: 1. The natural frequencies to avoid resonance 2. The mode shapes. The generally steel components are corrosive in nature and difficult for loading due to heavy weight and transportation of heavy structures are also difficult so there is need to replace these materials by new materials.